MEMBANGUN PEMAHAMAN MATEMATIKA SISWA SD MELALUI KARAKTERISTIK PERKEMBANGANNYA - Fitrianti, Yuli (Al 'Ilmi : Jurnal Pendidikan MIPA, 2012)
Students must learn  mathematics with understanding, actively building new knowledge from expeirience and prior knowledge. The students’ problems to build mathematics undeitanding is‘n cause balancingly between learning mathematisc and students’ deveopment thanicteristic, specially, elemantay school In this schcool,in this case the difficulty may be caused abtract concepts of mathematics and students’ characteristic that is apply thinking logic in concrete objects. In this journal described learning alternative to build mathematics understanding for elemantary school with students’ development characteristic.